PENGARUH BEBERAPA KONSENTRASI MOLASE TERHADAP KUALITAS AIR PADA AKUARIUM IKAN BANDENG - Meiza Putri; Fuad Muhammad; Jafron Wasiq Hidayat; Sapto Raharjo (Jurnal Akademika Biologi, 2016)
In 2013, the national aquaculture production is targeted to support the 14.8 million tons. One kultivan cultivated namely milkfish (Chanos chanos). Artificial feeding may lead to excessive tercernanya can not feed the fish, so that the necessary alternative fermented feed for fish growth. This study aims to assess the effect of several concentrations of molasses to the growth of fish. Research conducted in last August until October 2015. The method used is feeding pellets as much as 1 gram. Giving fermented feed ( molasses ) of 0 % , 2 % , 5 % and 7 % with three replications at 08.00 am today and measurement media quality water on the logs do every single week. Measurements were made using a DO meter, pH meter, thermometer and measuring Ammonia No3, No2, Fosfart, alkalinity and Tom were analyzed at the Laboratory of Physics - Chemistry BBPBAP. Analysis of the data used is using ANOVA test and Duncan Multile Range Test (DMRT). Results showed the effect of several concentrations Award (molasses) containing the bacteria Bacillus sp. and the most optimal pellet feed to the media quality of water present in a concentration of 2%. This is due to the lower molasses, can be absorbed by the fish so it is not the piling at the base of the aquarium. While the concentration of 5% and 7% are less than optimal. It thus allegedly because the feed is too much carbohydrates, can increase the potential for growth of pathogenic bacteria in the bottom of the aquarium